Surface plasmon resonance biosensors in the last decade: design strategies and improvements using nanomaterials - Donoso-Gonzalez, O (SPRINGER WIEN, 2026)
Surface plasmon resonance (SPR) biosensors have emerged as powerful analytical tools due to their label-free operation, real-time monitoring capability, and broad dynamic detection range, making them highly attractive for clinical, environmental, and food analysis. Despite significant progress over the past decade, the performance of SPR biosensors in real-world applications remains strongly limited by challenges related to sensor construction, surface functionalization, nanomaterial integration, and matrix effects in the analysis of complex samples. This review critically examines recent advances in SPR biosensor design with an emphasis on how construction strategies and functional nanomaterials influence analytical performance. Particular attention is given to the optimization of biomolecule immobilization and nanostructured interfaces as key factors governing sensitivity, selectivity, and robustness. Current limitations associated with nonspecific interactions and complex biological matrices are discussed, highlighting remaining gaps between laboratory performance and practical implementation. By addressing these challenges, this review provides a consolidated perspective on design principles required to improve the reliability and applicability of SPR biosensors, supporting their future development for clinically relevant diagnostics, environmental monitoring, and agronomic analysis.